2003
DOI: 10.1002/arp.213
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical prospection at Floridablanca archaeological site, San Julian Bay, Argentina

Abstract: We present the application of three geophysical methodsöground-penetrating radar, resistivity and electromagnetic inductionöto the Floridablanca archaeological site at San Julia¤ n Bay, Argentina. The objective of the prospection was to detect buried archaeological structuresömostly adobe wallsöto delimit these structures, tofindtheircharacteristicsandto study thepresence oftilesattributable to roof collapse within the zone of interest. Profiles were carried out in this zone and outside it to compare results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…In both cases, the blocks have a relative permittivity equal to 2 and conductivity equal to 0.003 S m À1 . The values of the conductivities correspond to those of Lascano et al (2003) and the values of the permitivities can be found in Daniels (1996) and Perez Gracia et al (2000).…”
Section: Electrical Modelmentioning
confidence: 94%
See 2 more Smart Citations
“…In both cases, the blocks have a relative permittivity equal to 2 and conductivity equal to 0.003 S m À1 . The values of the conductivities correspond to those of Lascano et al (2003) and the values of the permitivities can be found in Daniels (1996) and Perez Gracia et al (2000).…”
Section: Electrical Modelmentioning
confidence: 94%
“…The model is obtained from the information provided by the inversion of the geoelectrical profiles (Lascano et al, 2003): a sedimentary layer of 85 cm thickness, formed by clayed sand with relative permittivity equal to 4 and conductivity equal to 0.02 S m À1 , and below it, a layer of wet clay with relative permittivity equal to 10 and conductivity equal to 0.1 S m À1 . The adobe walls are embedded in the sedimentary layer at a depth of 12 cm and the height of these walls is 60 cm.…”
Section: Electrical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing use of GPR in archaeology over the last decades has been widely documented (Carcione, 1996;Conyers and Goodman, 1997;Pérez Gracia et al, 2000;Lascano et al, 2003;Conyers, 2004). A good overview was given by Owen (1995).…”
Section: Introductionmentioning
confidence: 93%
“…Although the geophysical methods have been applied systematically in archaeology during the last decades, their implementation in Argentina is relatively new, having started at the end of the 1990s (e.g., Lascano et al, 2003;De la Vega et al, 2005;Osella et al, 2005). In 2004 we have began an archaeo-geophysical study in Palo Blanco site, NW Argentina.…”
Section: Introductionmentioning
confidence: 99%